DEM Resolution Impact on the Estimation of the Physical Characteristics of Watersheds by Using SWAT - Waranyu Buakhao; Anongrit Kangrang (Advances in Civil Engineering)
A digital elevation model (DEM) is an important spatial input for automatic extraction of topographic parameters for the soil and water assessment tool (SWAT). The objective of this study was to investigate the impact of DEM resolution (from 5 to 90 m) on the delineation process of a SWAT model with two types of watershed characteristics (flat area and mountain area) and three sizes of watershed area (about 20,000, 200,000, and 1,500,000 hectares). The results showed that the total lengths of the streamline, main channel slope, watershed area, and area slope were significantly different when using the DEM datasets to delineate. Delineation using the SRTM DEM (90 m), ASTER DEM (30 m), and LDD DEM (5 m) for all watershed characteristics showed that the watershed sizes and shapes obtained were only slightly different, whereas the area slopes obtained were significantly different. The total lengths of the generated streams increased when the resolution of the DEM used was higher. The stream slopes obtained using the small area sizes were insignificant, whereas the slopes obtained using the large area sizes were significantly different. This suggests that water resource model users should use the ASTER DEM as opposed to a finer resolution DEM for model input to save time for the model calibration and validation.